THE DRILL TECHNIQUE IN SPEAKING CLASS FOR THE STUDENTS’ ENGAGEMENT - Arif Alexander Bastian; Eka Pratiwi Yunianti; Dyah Fitri Mulati; Defy Gustianing; Septika Ariyanti (IKIP Siliwangi, 2023)
This study sought to determine two things: I if speaking proficiency among students increased statistically significantly after they were taught using drill tactics, and (ii) the degree to which drill techniques were used to engage the students in speaking class. The pre-test, post-test, and observation all yielded data. The outcome revealed a statistically significant improvement in pupils' speaking abilities. The gain score was 14.06 and the significant level was (0.000.05), and the mean score improved from 58.00 on the pre-test to 72.06 on the post-test. The observation's findings revealed that the majority of pupils (79,02%) were actively participating in speaking class. This implies that even while drills encouraged students to speak out loud, they could only partially raise their level of pronunciation proficiency. Keywords: Drill Technique; Speaking; Teaching Speaking